Corporate Environmental Proactivity: Evidence from the European Union's Emissions Trading System - Andreou, Panayiotis; Kellard, Neil M. (My University, 2021)
In the presence of environmental policy, how do regulated firms respond? The answer is crucial for the design and effectiveness of policy regimes intended to mitigate environmental damage. We investigate whether particular types of firms are more likely to be proactive; in other words, which firms tend to behave in a manner most consistent with the desired policy outcomes. Using data on per-firm 'verified' and 'allocated' emissions from the European Union's Emissions Trading System (EU ETS) from 2005 till 2016, and given that some firms exceed or undershoot the allocated allowances by a large margin, we posit that this and related measures are useful proxies for a firm's proactiveness in responding to environmental policy. We find that public firms are less likely than private firms to be proactive, whilst the same is found for firms in common rather than civil law countries and for state-owned firms. Strikingly, proactiveness is associated both with greater reductions in greenhouse gas emissions and poorer firm performance, suggesting there is an economic cost to good environmental behaviour. Whilst the EU ETS is reducing emissions, it is not yet adequately compensating proactive firms or penalizing those who pollute - better system design could aid this further.
Keywords: Resource-based view; Entrepreneurial orientation; Strategies; Performance; Linking